2014
DOI: 10.2147/ijn.s70092
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity assessment of repeated intravenous injections of arginine–glycine–aspartic acid peptide conjugated CdSeTe/ZnS quantum dots in mice

Abstract: Background Nanotechnology-based near-infrared quantum dots (NIR QDs) have many excellent optical properties, such as high fluorescence intensity, good fluorescence stability, and strong tissue-penetrating ability. Integrin αvβ3 is highly and specifically expressed in tumor angiogenic vessel endothelial cells of almost all carcinomas. Recent studies have shown that NIR QDs linked to peptides containing the arginine–glycine–aspartic acid (RGD) sequence (NIR QDs-RGD) can specifically target integrin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 42 publications
3
18
0
Order By: Relevance
“…Oxidative stress has been regarded as a direct and mechanistic indicator of toxic potential (Shuhendler et al, ). It interacted with inflammation to promote both DNA damage and activated NF‐κB, inducing many acute or chronic liver and lung injury (Wang et al, ). The present study has been shown that ROS generated in response to RPS exposure caused lipid peroxidation and DNA damage (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress has been regarded as a direct and mechanistic indicator of toxic potential (Shuhendler et al, ). It interacted with inflammation to promote both DNA damage and activated NF‐κB, inducing many acute or chronic liver and lung injury (Wang et al, ). The present study has been shown that ROS generated in response to RPS exposure caused lipid peroxidation and DNA damage (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Although QDs have been utilised for stem cell tracking and imaging for many years [51][52][53][54][55][56][57][58], most toxicity and pharmacokinetic studies have focused on the behaviours of II B-VI A and III A-V A QDs in rodents [59]. Investigations of the IV A QDs are still in the early stages.…”
Section: Quantum Dotsmentioning
confidence: 99%
“…Sections (5 μm) of fixed liver tissue were cut using a rotary microtome. The sections were processed and passed through a graded alcohol series, dyed with hematoxylin and eosin, cleared in xylene, and inspected microscopically as described previously [20].…”
Section: Index Weight = Liver Weight/body Weight×100%mentioning
confidence: 99%